2011
DOI: 10.1186/1471-2326-11-4
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of efficacy and safety of intravenous ferric carboxymaltose (Ferinject) from clinical trial reports and published trial data

Abstract: BackgroundRecommendations given for intravenous iron treatment are typically not supported by a high level of evidence. This meta-analysis addressed this by summarising the available date from clinical trials of ferric carboxymaltose using clinical trial reports and published reports.MethodsClinical trial reports were supplemented by electronic literature searches comparing ferric carboxymaltose with active comparators or placebo. Various outcomes were sought for efficacy (attainment of normal haemoglobin (Hb)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
1
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 53 publications
(60 reference statements)
4
96
1
8
Order By: Relevance
“…5,[9][10][11] One reason for using the present approach was that ferric carboxymaltose (Ferinject) is safe to administer in high iron dosages (up to 1,000 mg at one time) and allowed a single visit for every patient. 12 Second, use of the Ganzoni formula may not be reliable in iPAH patients with hypoxemia-driven erythropoiesis and consequent hemoglobin (Hb) levels within the normal range despite iron deficiency. 11,13 Third, previous studies with iron therapy showed that the mean dose of iron needed was around 1,000 mg or even higher.…”
Section: Intravenous Iron Safely Increased Body Iron Stores and Qualimentioning
confidence: 99%
“…5,[9][10][11] One reason for using the present approach was that ferric carboxymaltose (Ferinject) is safe to administer in high iron dosages (up to 1,000 mg at one time) and allowed a single visit for every patient. 12 Second, use of the Ganzoni formula may not be reliable in iPAH patients with hypoxemia-driven erythropoiesis and consequent hemoglobin (Hb) levels within the normal range despite iron deficiency. 11,13 Third, previous studies with iron therapy showed that the mean dose of iron needed was around 1,000 mg or even higher.…”
Section: Intravenous Iron Safely Increased Body Iron Stores and Qualimentioning
confidence: 99%
“…В пределах ограничений данного исследования не наблюдалось почечной токсичности, нового развития сердечно-сосудистых или инфекционных событий. В этом ключе наиболее репрезентативной рабо-той является детальный обзор и метаанализ, опу-бликованный R.A. Moore, H. Gaskell et al, в рамках которого были проанализированы данные практи-чески всех исследований, в которых для коррекции анемии применялся препарат карбоксимальтозата железа [16]. Список исследований включал все про-екты и клинические испытания, в которых прини-мали участие хотя бы десять пациентов.…”
Section: òåìà íîìåðó / Cover Storyunclassified
“…Применение препарата изучено в большом чис-ле клинических испытаний у разных групп пациентов, при этом феррокинетика проанализирована с помощью позитронной эмиссионной томографии с целью оценки распределения железа после введения препарата [90]. Эффективность лечения препаратом подтверждена дан-ными, приведенными в систематическом обзоре и мета-анализе результатов рандомизированных исследований [91]. В многоцентровом рандомизированном контро-лируемом исследовании эффективность и безопасность инфузий карбоксимальтозата железа изучена у пациен-тов с вторичной ЖДА на фоне ВЗК [92].…”
Section: вопросы современной педиатрииunclassified